Studies on Traditional Uses of Plant Resources of Kanawar Wildlife Sanctuary, Kullu, Himachal Pradesh - Thakur, Suveena; Bhardwaj, Suneet (Indian Forester, 2017)
Kanawar Wildlife Sanctuary, one of the 33 sanctuaries of Himachal Pradesh, is situated in Parvati valley of Kullu district. It forms an important conservation unit in the vicinity of Great Himalayan National Park, Kullu and is a part of Great Himalayan National Park Conservation landscape. There are four villages inside Kanawar sanctuary. Besides local community Gaddis, a nomadic tribe of Himachal Pradesh, are also using various resources of the sanctuary for ages. The sanctuary harbours a wide range of plant diversity. It was found during the study that out of total 64 ethno-botanical plants found in the sanctuary 31 are used for curing various diseases of human beings, 6 are used for curing various ailments of animals, 2 are used as dyes and 8 are associated with socio-religious beliefs. Apart from these 16 plants are edible, 4 plants are used as fibres and 7 species are used for miscellaneous purposes. The uses in detail are described in detail with their botanical name, family, local name, part used, ailment and ethno-botanical use.